Konsep Perempuan dalam Budaya Dawan Mollo dan Relevansinya bagi Praktik Devosi kepada Bunda Maria dalam Komunitas Katolik di Kapan Mollo Utara - Siprianus Soleman Senda; Helidorus F. Anin; Patricius Neonnub; Hendriko Dicky Tae Della; Oswaldus Agusto Haki Mamulak; Rikardus Undat (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2026)
This study examines the relationship between the concept of women in the Dawan Mollo culture and the practice of devotion to the Virgin Mary in the Catholic community in Kapan, North Mollo. The urgency of this research lies in the need to understand how local cultural values ​​influence and are influenced by religious beliefs, particularly in the context of women's roles. The primary objective of this study is to explore the intersection of women's values ​​in the Dawan Mollo culture with the figure of the Virgin Mary in the Catholic tradition. This study will analyze how the practice of devotion to the Virgin Mary reflects or reinterprets the concept of women in the local culture. The method used is a qualitative approach using observation, in-depth interviews, and literature review. Research participants included traditional leaders, community leaders, religious leaders, and women in the Dawan Mollo Catholic community. The results show that the concept of women in Mollo culture influences the Kapan Catholic community's understanding of the role of Mary and their devotion to her.